2010
DOI: 10.1287/orsc.1090.0434
|View full text |Cite
|
Sign up to set email alerts
|

Go (Con)figure: Subgroups, Imbalance, and Isolates in Geographically Dispersed Teams

Abstract: Research regarding geographically dispersed teams (GDTs) is increasingly common and has yielded many insights into how spatio-temporal and socio-demographic factors affect GDT functioning and performance. Largely missing, however, is research on the effects of the basic geographic configuration of GDTs. In this study, we explore the impact of GDT configuration (i.e., the relative number of team members at different sites, independent of the characteristics of those members or the spatial and temporal distances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
213
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(223 citation statements)
references
References 117 publications
6
213
2
2
Order By: Relevance
“…This perspective has already been employed by studies on virtual teams in non IT settings [18,48]. We extend this to the IT domain.…”
Section: Theoretical and Practical Contributionmentioning
confidence: 98%
See 1 more Smart Citation
“…This perspective has already been employed by studies on virtual teams in non IT settings [18,48]. We extend this to the IT domain.…”
Section: Theoretical and Practical Contributionmentioning
confidence: 98%
“…They found that subgroups form and that conflict is heightened and trust is decreased between the geographically dispersed subgroups. Another exception is O'Leary and Mortensen [48] that found that geographically based subgroups weaken team identification, lead to less effective transactive memory and increase team conflict.…”
Section: Distributed Teams As Example For Subgroups In Software Develmentioning
confidence: 99%
“…We found that because English had to be brought into play in order for the teams to interact, members of the LFS subgroups felt relatively intimidated and less powerful compared to those in the FS subgroups (see Table III). The LFSs, particularly in Teams A and B, apparently perceived a significant disadvantage due to their inability to contribute to and influence team interactions as much as their FS counterparts (O'Leary and Mortensen, 2010). Thus an in-group/out-group mentality started to emerge, along the lines shown in Table IV We suggest that fluency inequalities create the need for subordinate subgroups to seek to even out the imbalance and perceived power loss, and posit that rule emergence is a strategy in response to the subjective superiority/inferiority comparisons between subgroups to gain a more assertive identity (Tajfel and Turner, 1986).…”
Section: Language Faultlinesmentioning
confidence: 99%
“…Team size, role descriptions and role distribution are among those characteristics in distributed teams that can influence team coordination and communication and therefore team performance (e.g. [7], [13], [14], [15]). For example, Kofman and Klinger [16] suggest that role confusions (meaning the confusion caused by the difference between how the role is described and what people actually do within the role) may affect team performance and communication.…”
Section: Background Theorymentioning
confidence: 99%